(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
Jwara is a disease which affects the body, mind, senses simultaneously. It diminishes the intelligence, strength, complexion and enthusiasm of the sufferer and produces exhaustion, exertion and aversion to food. It should be treated considering its Avastha, causative factors and involved Dosha. Factors which are responsible for the manifestation of Jwara are the three Sareerika Doshas and two Manasika Doshas. Without the involvement of these Doshas, living beings do not get afflicted with Jwara. Abnormal functioning of Jataragni gives rise to Ama which vitiates Rasa dhatvagni. This produces Samavastha and vitiates Rasavaha Srotas. In Jwara, Swedavaha Srotas also gets affected as the vitiated Dosha along with Ama, blocks the Srotas giving rise to raised body temperature. Such an important disease should be understood clearly as the guidelines laid down in the context of Jwara to diagnose different pathological states are employed elsewhere and guides the physician to select the best line of management. Here the Chikitsa sutra Vivechana of Nava Jwara has been elaborated in detail through which Jwaragna, Deepana, lightness of body, alleviation of the aggravated Dosas, appearance of Kshut and such benefits are all achieved.